Médée et les serpents - Dognini, Cristiano (Gerión. Revista de Historia Antigua, 2003)
The victory of Medea on the dragon is known in ltaly in the VII century B.C., thence three passages of Columella (X 367-368), Hyginus (Fab. XXVI 3) and Servius (ad Aen. VII 750) may show an Etruscan ceremonial, because they present Etruscan peculiarities and relate the fight of Medea against the snakes.